A Case-Control Study to Estimate the Effectiveness of Maternal Pertussis Vaccination in Protecting Newborn Infants in England and Wales, 2012–2013. (19th October 2014) - Dabrera, Gavin; Amirthalingam, Gayatri; Andrews, Nick; Campbell, Helen; Ribeiro, Sonia; Kara, Edna; Fry, Norman K.; Ramsay, Mary
Abstract : This case-control study demonstrated that maternal pertussis vaccination was highly effective in preventing laboratory-confirmed pertussis infection in infants aged <2 months during a national pertussis outbreak in England and Wales. Abstract: Background.  Infants with pertussis infection are at risk of severe clinical illness and death. Several countries, including the United Kingdom, have introduced maternal pertussis vaccination during pregnancy to protect infants from infection following national increases in pertussis notifications. The objective of this study was to estimate the effectiveness of maternal pertussis vaccination in protecting infants against laboratory-confirmed pertussis infection. Methods.  A case-control study was undertaken in England and Wales between October 2012 and July 2013. Cases were infants aged <8 weeks at onset with pertussis infection tested by real-time polymerase chain reaction or culture. Family doctors of each case were asked to identify healthy infants born consecutively after the case in each practice, to act as controls. Fifty-eight cases and 55 controls were included in this study. Odds ratios (ORs) were calculated for the association between maternal vaccination and infant pertussis infection. The vaccine effectiveness (VE) was calculated as 1 – OR. This was adjusted for sex, geographical region, and birth period. Results.  Mothers of 10 cases (17%) and 39 controls (71%) received pertussis vaccine in pregnancy. This gave an unadjusted VE of 91% (95% confidence interval [CI], 77%–97%). Adjusted VE was 93% (95% CI, 81%–97%). Conclusions.  Maternal pertussis vaccination is effective in preventing pertussis infection in infants aged <8 weeks and may be considered in other countries experiencing high levels of pertussis notifications.